The weather machine : a journey inside the forecast - Blum, Andrew (Ecco, an imprint of HarperCollinsPublishers, 2019)
The weather is the foundation of our daily lives. It<U+2019>s a staple of small talk, the app on our smartphones, and often the first thing we check each morning. Yet behind these quotidian interactions is one of the most expansive machines human beings have ever constructed<U+2014>a triumph of science, technology and global cooperation. But what is this <U+2018>weather machine<U+2019> and who created it? In The Weather Machine, Andrew Blum takes readers on a fascinating journey through an everyday miracle. In a quest to understand how the forecast works, he visits old weather stations and watches new satellites blast off. He follows the dogged efforts of scientists to create a supercomputer model of the atmosphere and traces the surprising history of the algorithms that power their work. He discovers that we have quietly entered a golden age of meteorology<U+2014>our tools allow us to predict weather more accurately than ever, and yet we haven<U+2019>t learned to trust them, nor can we guarantee the fragile international alliances that allow our modern weather machine to exist. Written with the sharp wit and infectious curiosity Andrew Blum is known for, The Weather Machine pulls back the curtain on a universal part of our everyday lives, illuminating our relationships with technology, the planet, and the global community.